Monitoring of earthquakes in Central Tuva - Kuzhuget, Kalin-ool S.; Mongush, Say-Suu S. (The New Research of Tuva, 2014)
Article reviews the issues of monitoring the earthquakes in Tuva. Monitoring has been conducted by integrated study of geodynamics and seismicity geoblock by placing seismic stations configured for registration of local and distant earthquakes. As part of the network has five stationary points: Kyzyl, Turan, Chadan, Erzhey, Samagaltai.
Keywords: Central Tuva; earthquakes; microseismic zoning; monitoring; shagonar node